ANALISIS KESEJAHTERAAN MAQASHID SYARIAH PADA USAHA MIKRO KECIL MENENGAH - SAFARINDA IMANI (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2019)
The contribution of the Surabaya city government is an provision of freedom of production based on the levelof creativity and innovation. Building Suroboyo bridges, dancing fountains, bulak parks, and ﬁsh centersthat make up the area to better place towards prosperity. MSMEs will also increase regional income. MSMEsindirectly apply maqashid sharia. Using qualitative descriptive analysis to understand how MSM can be used in the perspective of Islamic economics from the side of Maqashid al-Shari'ah.